Re-actualization of Quran’s Perfection: Questioning the Concept of Ali Abdul Halim Mahmud’s Quranic Education - Arif, Mahmud (Proceeding International Conference on Religion, Science and Education, 2022)
The Quran is believed to be an eternal marvel with teachings that shall remain relevant regardless of the time and place. Such a fundamental conviction has led to various perspectives and lively discussions. Some consider the Quran as an open text that can continuously be reinterpreted, while the others consider it as the ultimate book that provides guidance concerning all matters of human life. Given this context, it is of great interest to critically discuss the views of Ali Abdul Halim Mahmud who considered the Quran as a comprehensive source of guidance for addressing the various problems of life as well as a text filled with a myriad of educational prescriptions. Based on this assumption, Mahmud actively elaborated his views on the Quran’s perfection and the inevitability of Muslims to relentlessly abide by it. He believed that the solution for Muslims, who are currently suppressed by a broken and deceptive system, is none other than returning to the guidance of the Quran and the Sunnah.